Plasma cholesterol concentration and extra lipid band in monoclonal gammopathies. Issue 705 (July 1984) - Levy, Y.; Aviram, M.; Spira, G.; Tatarsky, I.; Brook, G. J.; Carter, A.
Abstract : Plasma lipids and lipoproteins were studied in 21 patients with benign monoclonal gammopathy, 21 patients with multiple myeloma and seven patients with Waldenström's macroglobulinaemia. Results were compared with those of a control group, age and sex matched. Low plasma cholesterol levels in all three patient groups were associated with low HDL-cholesterol concentrations. Apo A-I, but not apo B, was significantly reduced. Sixty per cent of the patients exhibited an extra lipid band on plasma lipoprotein electrophoresis, which could be an immunoglobulin-lipid complex. In these patients plasma and LDL-cholesterol levels were significantly lower than in those patients in whom this band was absent. No correlation was found between the severity of the disease and plasma lipid pattern.